Pengembangan Aplikasi Laporan Bulanan Berbasis VBA Macro Excel di Kantor Urusan Agama Kecamatan Kadudampit-Sukabumi (Current Research in Education: Conference Series Journal, 2023)
The Office of Religious Affairs is one of the institutions that facilitates the community in managing various needs related to services and administration. At the end of each month KUA must recapitulate data which will then be deposited to the central institution, usually monthly reports are made manually by inputting data one by one and of course it takes quite a long time because it must meet various formats. so it is hoped that the process of managing monthly reports can be carried out more effectively and efficiently. The purpose of this research is to create a software that can assist in the preparation of monthly reports from the KUA Kadudampit District. The method used in making the application is the Agile Software Development method while in making the application using a VBA Macro connected to Ms. Office Excel. The results of the study stated that there is a need for an application system that helps in completing monthly reports to make performance time more effective, therefore the authors create a system that can automate the creation of monthly reports. With the monthly report application, it is expected to reduce the time in the data entry process automatically, speed up the process of filling out various formats, reduce errors in data input and the system can be used repeatedly.